THE IMPACT OF VIRTUAL LABORATORY INTEGRATED INTO HYBRID LEARNING USE ON STUDENTS’ ACHIEVEMENT - Solikhin, Febrian; Sugiyarto, Kristian Handoyo; Ikhsan, Jaslin (SCAD Independent, 2019)
The virtual laboratory for electrochemistry materials has been developed. The characteristic of this virtual chemistry laboratory associated with the effect on students? achievement was analyzed. Thus this type of research was research and development by using ADDIE development model. In the implementation, the phase of the product was the quasi experimental method with a post-test only design. Classes used for this study were 3 classes, first-class using traditional laboratory, a second class using only virtual laboratory, and the third class using traditional laboratory and virtual laboratory as a supplement. All three classes were performed by the same teacher and the learning time. The instrument used to see the effect of the virtual laboratory was a test instrument. While the instrument used to assess the quality of the media was a questionnaire assessment. The results of this study were a developed virtual laboratory that can be operated via the web on smartphones and computers. In addition, the results of the assessment by the chemistry teachers stated that the virtual laboratory was in good quality and in classroom studies, the third and first classes showed significant differences. In the future research virtual laboratory as a supplement in other subject, matters can be developed.